School shootings, the media, and the spatialities of dark belonging - Juha Ridanpää (Fennia: International Journal of Geography, 2024)
This article discusses how news reports attendant to crisis events are used by the media to construct the logic of inclusion and exclusion. The focus of the paper is on rampage school shootings, which represent an illustrative example of how emotions and socio-politics become entwined in a spatial manner. The article also discusses how parties involved in the shooting event – the perpetrator, victims and the bereaved – are profiled in news reports as narrative characters through which the logic of inclusion and exclusion is constructed and conveyed, in different ways, and various spatial scales. This article illustrates how the media narratives of school shootings engage readers with the logic of belonging, offering normative understandings of how belonging and non-belonging should be comprehended. This paper contributes to both the geographical studies of belonging and media research.